IT strategies for Business competitiveness in Bangladesh - Rahman, Ziaur (BRAC University, 2010)
In the growth envelope, Information & Communication Technology plays the facilitating role of revitalizing the competitiveness of businesses across any country. This article offers a pedagogical perspective on ICT enabling strategies that need to be catered to and assimilated in Bangladeshi enterprises for enhancing their competitiveness in the global frontier. This study takes a macro level perspective on the focus of ICT education and its professional concentration at levels in Bangladesh. However, this article depicts the unbalanced educational thrust that is not alleviating the true scope of business competitiveness in Bangladesh. The findings from this articles show that economic stability and ICT infrastructure is not only required for effective and efficient development of the nation but also a culture of technology affiliation among the resource starved nation and a strategic plan for guiding the ICT sector is a must. Using primary and secondary market data, governmental policies, private and public initiatives, this article offers a picture of contemporary ICT environment, its shortcomings, association with the affairs of business development in Bangladesh and, finally, strategies for advancement among the landscape of different nations.